2021
DOI: 10.1038/s41699-021-00213-4
|View full text |Cite
|
Sign up to set email alerts
|

Controllable potential barrier for multiple negative-differential-transconductance and its application to multi-valued logic computing

Abstract: Various studies on multi-valued-logic (MVL) computing, which utilizes more than two logic states, have recently been resumed owing to the demand for greater power saving in the current logic technologies. In particular, unlike old-fashioned researches, extensive efforts have been focused on implementing single devices with multiple threshold voltages via a negative-differential current change phenomenon. In this work, we report a multiple negative-differential-transconductance (NDT) phenomenon, which is achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…With this finding of L-NDT, a light-triggered ternary inverter has been proposed, showing the capability for optoelectronic MVL circuits. 151 In addition to the advancement in high-performance and novel optoelectronic devices, the prototype of multifunctional p-n heterostructures that operate as diodes, transistors, and photodetectors has been recently demonstrated. Cheng et al constructed a Gr/hBN/MoS 2 /MoTe 2 heterostructure and demonstrated the three operation functions in one device.…”
Section: Light-triggered Modementioning
confidence: 99%
See 1 more Smart Citation
“…With this finding of L-NDT, a light-triggered ternary inverter has been proposed, showing the capability for optoelectronic MVL circuits. 151 In addition to the advancement in high-performance and novel optoelectronic devices, the prototype of multifunctional p-n heterostructures that operate as diodes, transistors, and photodetectors has been recently demonstrated. Cheng et al constructed a Gr/hBN/MoS 2 /MoTe 2 heterostructure and demonstrated the three operation functions in one device.…”
Section: Light-triggered Modementioning
confidence: 99%
“…Shim et al attributed this to the variation of the potential barrier at the Gr/WSe 2 junction under gating voltages, which affected photocarrier collections at the source/drain electrodes. With this finding of L‐NDT, a light‐triggered ternary inverter has been proposed, showing the capability for optoelectronic MVL circuits 151 . In addition to the advancement in high‐performance and novel optoelectronic devices, the prototype of multifunctional p–n heterostructures that operate as diodes, transistors, and photodetectors has been recently demonstrated.…”
Section: Reconfigurable P–n Heterostructuresmentioning
confidence: 99%
“…Recently, Seo et al introduced an additional partial gate and laser power/wavelength to form an adjustable potential barrier/well to enable control of the collection of carriers in the WSe 2 channel, suggesting the NDT transfer characteristic with an “N” shape. 157 Particularly, the introduction of various laser wavelengths precisely promoted the modulation of the NDT effect, resulting in multiple NDT operations. Therefore, the authors accordingly designed a ternary NAND/NOR gate by exploiting the double NDT effect enabled by the partial gate and input lasers, as displayed in Fig.…”
Section: Logic Gate and Integrated Circuit Enabled By Tmd Fetsmentioning
confidence: 99%
“…Negative differential resistance (NDR)-based electronic devices have drawn considerable attention for various applications, such as oscillators, amplifiers, , and multi-valued logic because of the versatility of their folded current–voltage ( I – V ) characteristics. The concept of NDR in solid-state electronics was first observed in a crystal detector by Eccles and Pickard in 1909.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, NDR studies based on band-to-band tunneling (BTBT) in van der Waals (vdW) heterojunction structures fabricated on two-dimensional (2D) transition metal dichalcogenides (TMDCs) have achieved significant progress due to the atomic-scale thickness and excellent interface quality of the TMDCs. , In general, the NDR performance is mainly determined by the peak-to-valley current ratio (PVCR) of the NDR curve and the current and voltage levels of its peaks and valleys. A high PVCR provides a wider range of middle states in multivalued logic (MVL) applications. In addition, a higher peak current density ( J peak ) and controllable peak and valley voltages ( V peak/valley ) in NDR devices are also desirable in practical applications. ,,,, In MVL applications, J peak and V peak/valley determine the input/output voltage range. However, recently reported BTBT-based NDR devices exhibit insufficient PVCR and J peak and lack controllability over V peak/valley , which are directly related to NDR performance. ,, The BTBT-based NDR devices induce NDR by interrupting the transport of tunneling carriers through the energy band alignment of the heterojunction of TMDCs.…”
Section: Introductionmentioning
confidence: 99%